The Managerial Role of the Principal in Developing a Character-Based Excellent Elementary School: A Case Study at School in Bojonegoro - Himmatin, Ulya; Khayati, Nur (Journal of Education and Religious Studies, 2025)
In order to respond to the development of the times, the principal of Muhammadiyah 3 ICP Bojonegoro Elementary School strives to make the institution he leads a superior school with character. This study aims to uncover new facts about the programs implemented by the principal in realizing a superior chartered school and his managerial role. The method used is qualitative with a descriptive research type. The results found indicate that: (1) the principal implements various strategic programs that not only focus on academic achievement but also on character building. The programs are listed in eight things, namely: a) Immersion program, b) Full day education, c) congregational prayer, d) DEAR TIME, e) blessed Friday, f) outdoor learning activity, g) Tahsin and Tahfidz class, and h) Open house. (2) The role carried out by the principal includes various managerial, pedagogical and social aspects, including: a) determining the vision and mission b) developing a character-based curriculum, c) developing human resources, d) developing a supportive school environment, e) collaboration with other levels and parents, f) monitoring and evaluation. This role can be seen in the creation of a family-like and open work environment, and the dissemination of information regarding the school's vision, mission, and program implementation to all members of the school community. This study makes an academic contribution to the field of educational management by providing empirical evidence on the practices of managing character-based superior schools at the elementary education level. The findings enrich scholarly discourse on the managerial role of school principals in systematically integrating academic achievement with character education, and may serve as a conceptual and practical reference for the development of policies and the implementation of character-based superior school programs in other educational institutions.